Data analysis for image transmitted using Discrete Wavelet Transform and Vector Quantization compression - Mustapha Khelifi; Abdelmounaim Moulay Lakhdar; Iman Elawady (Universitas Ahmad Dahlan, 2016)
In this paper we are going to study the effect of channel noise in image compressed with vector quantization and discrete wavelet transform. The objective of this study is to analyze and understand the way that the noise attack transmitted data by doing lot of tests like dividing the indices in different levels according to discrete wavelet transform and dividing each level in frames of bits. The collected information well helps us to propose solutions to make the received image more resistible to the channel noise also to benefit from the good representation obtained by using vector quantization and discrete wavelet transform.